Condition of Seagrass Meadows in The Waters Around The Sunrise Tourist Area, Makalisung Village, Kombi District, Minahasa Regency - Baso, Fathan; Wagey, Billy T.; Sondak, Calvyn F. A.; Ginting, Elvy L.; Tilaar, Sandra O.; Rampengan, Royke M. (JURNAL PESISIR DAN LAUT TROPIS, 2026)
Seagrass is a flowering plant (magnoliopyta). Seagrass requires a minimum light intensity of $11% - 25%$ for photosynthesis, and disturbances can reduce the availability of light. Research in the Sunrise Tourism Area, Makalisung Village, aims to identify the types and conditions of seagrass meadows, considering the pressure from human activities such as garbage disposal and fishing boat traffic. The data collection method uses quadrant transects with three 100-meter transects, each placed in 11 quadrants. The results of the study successfully identified 7 types of seagrass, including Cymodocea rotundata, Enhalus acoroides, Halophila ovalis, Halodule pinifolia, Halodule uninervis, Syringodium isoetifolium, and Thalassia hemprichii. Based on calculations, the average percentage of seagrass cover is 57.68% and can be categorized as dense. However, although the cover is classified as dense, Meanwhile, according to the Ministry of Environment Decree No. 200/2004, the determination of the closure of seagrass meadow conditions can be categorized as less rich/less healthy. This indicates the potential for environmental problems that can affect the health of the seagrass ecosystem at Sunrise Beach. Keywords: seagrass condition, Sunrise Beach, coastal waters, seagrass cover Abstrak Lamun (seagrass) merupakan tumbuhan berbunga (magnoliopyta). Lamun memerlukan intensitas cahaya minimal $11% - 25%$ untuk fotosintesis, dan gangguan tersebut dapat mengurangi ketersediaan cahaya. Penelitian di Kawasan Wisata Sunrise, Desa Makalisung, bertujuan mengidentifikasi jenis dan kondisi padang lamun, mengingat adanya tekanan dari aktivitas manusia seperti pembuangan sampah dan lalu lintas perahu nelayan. Metode pengambilan data menggunakan transek kuadran dengan tiga transek sepanjang  100 meter, masing- masing diletakkan 11 kuadran. Hasil penelitian berhasil mengidentifikasi 7 jenis lamun, termasuk Cymodocea rotundata, Enhalus acoroides, Halophila ovalis, Halodule pinifolia, Halodule uninervis, Syringodium isoetifolium, dan Thalassia hemprichii.Berdasarkan perhitungan, rata-rata persentase tutupan lamun adalah 57,68% dan dapat dikategorikan padat.Namun, meskipun tutupan tergolong padat, Sedangkan menurut KEPMEN KLH No 200/2004, penentuan penutupan kondisi padang lamun dapat dikategorikan dalam kategori kurang kaya/kurang sehat. Hal ini menunjukkan adanya potensi masalah lingkungan yang dapat memengaruhi kesehatan ekosistem lamun di Pantai Sunrise. Kata kunci: kondisi lamun, Pantai Sunrise, perairan pesisir, tutupan lamun